An exploration of the availability, development and use of learning support materials on waste management in Kwazulu-Natal : a case study - Manqele, Mbaweni Beauty (Rhodes University, Faculty of Education, Department of Education, 2006)
This case study was done in KwaZulu"“Natal province in South Africa within two municipalities Ethekwini and Umsunduzi Municipality. Three communities participated in this study. The research is motivated by the lack of cooperation between some municipalities and Community Based Organisations (CBOs) in implementing the National Waste Management Strategy (NWMS) at a local level. The primary goal is to explore the availability and development of learning support materials (LSMs) that relates to waste management in collaboration with CBOs and local councillors. The secondary goal is to explore the use of learning support material to promote participation in the implementation of the NWMS. Coresearchers were from the Community Based Organisations as well as local councillors who are located within the communities of these CBOs. Pseudonyms for co-researchers from CBOs and Councillors and the name of their townships have been used to protect co-researchers. A literature review has been conducted to explore research that has been done on the development, usage, accessibility and distribution of the LSMs. Data collection methods included semi-structured interviews; field visits to communities, tape recording of discussions and the keeping of a field journal. Some of the key findings included that LSMs is used by both CBOs and Councillors to try to reduce local environmental problems. It also identified that there are no formal mechanisms between CBOs and Municipalities in dealing with waste management programmes within the identified communities. The other important finding was that the participation of CBOs in the development of LSMs normally excludes the user groups as a result language used is not always understood. Illustrations used in some cases may be misinterpreted if the reader is not English literate as most of material in circulation is written in English. Some recommendations for further research have been made in relation to the findings made in the study. These included recommendations on the development, usage of LSMs, participation of stakeholders in resource development within the context of CBOs and local municipalities.
Keywords: Waste disposal in the ground -- South Africa -- KwaZulu-Natal; Waste products -- Government policy -- South Africa; Refuse and refuse disposal -- Government policy -- South Africa; Refuse and refuse disposal -- Environmental aspects -- South Africa -- KwaZulu-Natal; Refuse and refuse disposal -- South Africa -- KwaZulu-Natal; Hazardous wastes -- Management -- South Africa -- KwaZulu-Natal; Hazardous waste sites -- Government policy -- South Africa; Environmental education -- South Africa -- KwaZulu-Natal; Teaching -- Aids and devices -- South Africa